Occupational Stress of Farm Scientists Working in Agricultural Universities - Chandan Kumar Panda; Sarthak Chowdhury (Indian Journal of Extension Education, 2018)
Right from the day of entering into service till the day of retirement, a farm scientist is invariably exposed to various stressful situations for one reason or others. In the field of work and organizational psychology, too, the concept of stress has obtained its own position under job stress. Stress is the mental and physical condition. The stress of the farm scientists was measured through the Occupational Stress Indicator (OSI) scale of Cooper et al. (1987) and Job Satisfaction was measured with the Quin and Shepard (1974) Scale. This research work was conducted in Bidhan Chandra Krishi Viswavidyalaya and Uttar Banga Krishi Viswavidyalaya. The complete enumeration method was followed and sample size was ninety six. Major contributing factors associated with the occupational stress of the farm scientist were organizational communication, task performance, skills utilization and psychological “feel” in organization and out of these four factors task performance was the best single predictor of job satisfaction in relation to OSI. Twenty two variables were clustered in six factors.